Magnesium lithospermate B promotes proliferation and differentiation of neural stem cells in vitro and enhances neurogenesis in vivo. (August 2018) - Zhang, Zhang; Wang, Zichen; Rui, Wei; Wu, Shiwei
Highlights: Magnesium lithospermate B induces generation of more neuronal cells and less glial cells from neural stem cells in vitro. Magnesium lithospermate B enhances local neurogenesis. Motor function is significantly improved in magnesium lithospermate B-treated Parkinson's Disease models. Abstract: Multipotent neural stem cells could generate neurons and glial cells. Wide studies have been conducted to disclose the mechanism underlying neural stem cell differentiation and multiple factors have been identified in this field, one of which is bioactive components including natural herbal medicine. In this study, we found that magnesium lithospermate B is able to promote proliferation of neural stem cell in vitro. Besides, magnesium lithospermate B also induces generation of more neuronal cells and less glial cells. The in vivo studies indicates that magnesium lithospermate B enhances local neurogenesis since more Ki67+ and Thy1+ cells are observed in hippocampal region with injection of magnesium lithospermate B. Interestingly, enhancing proliferation and neurogenesis occurs in medial forebrain bundle of Parkinson's Disease model and behavioral studies demonstrates that motor function is significantly improved in magnesium lithospermate B-treated disease models. Furthermore, we also found that effect of MLB on proliferation and differentiation of NSCs was mediated by PI3K/Akt signaling. Collectively, our study shows the important role of magnesium lithospermate B in neural stem cell proliferation and differentiation, accordingly providing a simple and efficient method to induce the neuronal cell generation in neurodegenerative disease model.